Evaluating Novel Diagnostics in an Outbreak Setting: Lessons Learned from Ebola - Pollock, Nira R. (J Clin Microbiol, 2017)
Inadequate access to rapid testing for Ebola virus disease during the 2014-to-2016 outbreak led to an explosion in the development of diagnostics that could be performed at or near the point of care and by less-experienced operators, leading in turn to an acute need for novel test evaluation. Here, we present the challenges to development and evaluation of novel diagnostics in an emergency setting and suggestions for potential new “global emergency standards” to address them.